Quantitative Microbiological Study of Subgingival Plaque by Real-Time PCR Shows Correlation between Levels of Tannerella forsythensis and Fusobacterium spp. - Suzuki, Nao (American Society for Microbiology, 2004)
A TaqMan-based real-time PCR assay was established to quantify the periodontopathic bacteria Tannerella forsythensis and Fusobacterium spp. With this assay, the prevalence and proportion of these bacteria in clinical specimens were evaluated. Our preliminary results suggest a positive colocalization of T. forsythensis and Fusobacterium spp. in periodontal pockets.